2021
DOI: 10.1029/2020jg006027
|View full text |Cite
|
Sign up to set email alerts
|

Slope‐Aspect Induced Climate Differences Influence How Water Is Exchanged Between the Land and Atmosphere

Abstract: Plant transpiration is a major conduit for the transfer of water from the land to the atmosphere (Jasechko et al., 2013). Recent studies have advanced our understanding of how complex and sensitive the leaf-to-atmosphere link is to localized feedbacks, such as slope exposure and associated conditions (e.g., Amitrano et al., 2019;Harrison et al., 2020;Link et al., 2014). Microclimates have been highlighted in particular as a distinct control on long-term ecosystem vulnerability, separate from evolving macroclim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…While primarily focused on determining the importance of soil type and geomorphology of the region, the study's most prominent finding is that shrubs growing on east and east north east facing slopes had significantly higher total plant volume and distance between neighbors than on any other slope face. Slopes in the region studied by Gearon and Young (2021) were much less steep, on average, than those studied by Bilir et al (2021). Thus, such an extreme gradient in light environment or available soil moisture would not expected.…”
Section: Microclimate Morphology and Ecosystem Structurementioning
confidence: 75%
See 4 more Smart Citations
“…While primarily focused on determining the importance of soil type and geomorphology of the region, the study's most prominent finding is that shrubs growing on east and east north east facing slopes had significantly higher total plant volume and distance between neighbors than on any other slope face. Slopes in the region studied by Gearon and Young (2021) were much less steep, on average, than those studied by Bilir et al (2021). Thus, such an extreme gradient in light environment or available soil moisture would not expected.…”
Section: Microclimate Morphology and Ecosystem Structurementioning
confidence: 75%
“…Yet, during times of soil dry down (soil water content < 4.5%) latent heat flux (LE) as measured by identical above-canopy eddy covariance systems in each forest is up to 25% greater in the unaltered forest than in the disturbed (Figure 1). In an in silico "forcing condition swap" between the two sites, similar to that performed by (Bilir et al, 2021), it was shown that these differences were unable to be accounted for by the minor differences in temperature, light, vapor pressure deficit, or soil water conditions between the two forests (Matheny et al, 2014). The hydraulic strategies, defined as the distinct patterns of water acquisition, storage, and use, of the principle tree species comprising each plot were indicated as the most probable cause for the sustained differences in LE during periods of water limitation (Matheny et al, 2015;Matheny, Fiorella, et al, 2017).…”
Section: Divergent Responses To Stressorsmentioning
confidence: 99%
See 3 more Smart Citations